On Numerical Simulations of Turbulent Flows over a Bluff Body with Aerodynamic Flow Control Based on Trapped Vortex Cells: Viscous Effects - Dmitry A. Lysenko (Fluids)
Turbulent flows over a semi-circular cylinder (a limiting case of a thick airfoil with a chord equal to the diameter base) are investigated using high-fidelity large-eddy simulations at a diameter-based Reynolds number, Re = 130,000, Mach number, M = 0.05, and a zero angle of attack. The aerodynamic flow control system, designed with two trapped vortex cells, achieves a complete non-separated flow over the bluff body, except for low-scale turbulence effects, reaching approximately 80% of the theoretical lift coefficient limit (<semantics>2π</semantics> for the half-circular airfoil). Viscous effects are analyzed using the conventional Reynolds-averaged Navier–Stokes approach for a broad range of Reynolds numbers, 75,000 ≤ Re ≤ 1,000,000. Numerical results demonstrate that the aerodynamic properties of the implemented concept are independent of the Reynolds number within this interval, highlighting its significant potential for further development.